Ethnomathematics studies: Mapping and construction of culture-based teaching materials - Andi Saparuddin Nur; Kartono Kartono; Zaenuri Zaenuri; Rochmad Rochmad (Universitas Negeri Semarang, 2022)
Mathematical ideas are often found in community activities and culture. Researchers have paid much attention to ethnomathematical studies describing mathematical ideas in culture. However, the mapping and construction of Makassar culture-based mathematics teaching materials have not been widely explored. This study aims to map and construct culture-based mathematics teaching materials through ethnomathematical studies. This type of research is a qualitative study with an ethnographic approach. The subject of this research is the Jeneponto community with Makassar ethnic background. The research instrument used observation sheets, interview guides, voice recorders, and field notes. Observation of cultural objects focuses on salting methods, fishing methods, time systems, forms of craft, and the use of horses. The results show that mathematical ideas are used in various activities and cultures of society. Mathematical concepts are connected with various cultural objects: numerical systems, lines and angles, plane figures, spatial figures, statistics, sequences and series, social arithmetic, and algebra. Activity-based task sheets, project assignments, modules, and field observation reports are forms of culture-based teaching materials in harmony with the ethnomathematical model as a learning innovation. The findings in this study propose integrating culture-based teaching materials in the ethnomathematical learning model.